Estadísticos vitales de bemisia tabaci biotipo b en frijol e interacción con el parasitoide amitus fuscipennis (2009)
Life-history parameters of the whitefly Bemisia tabaci biotipo B were determined at laboratory conditions at 26 °C ± 2 °C y 80 ± 5 % de RH on bean ICA-Pijao. Mean longevity of the whitefly was 34 ± 1,64 days, mean total fecundity was 211,4 ± 15,1 eggs per female with a daily oviposition rate of 6,1 ± 0,28 eggs per day. Net reproduction rate was 137,8. Generation Time was 43,8 days and the intrinsic rate of population increase rm was 0,125. These values are according to previous ones reported and support usefulness of ICA-Pijao bean for B. tabaci rearing. It was not possible to rear Amitus fuscipennis from B. tabaci. Behaviour studies showed that the parasitoid stayed only average 617,3 s on whitefly infested leaflets. It invested most of the time walking (46,4%), preening (35,6%) and standing still (16,7%). A. fuscipennis just touched accidentally one nymph once but it neither drummed it with the antenna nor laid an egg. Results indicated that A. fuscipennis is not a potential natural enemy of B. tabaci biotipo B.